Modified Starch-Based Materials for Sustainable Food Packaging - Isnainul Kusuma; Safinta Nurindra Rahmadhia; Alfian Ma'arif; Agus Aktawan; Titisari Juwitaningtyas; Nor Hanuni Ramli; Samuel Olugbenga Olunusi (Universitas Ahmad Dahlan, 2026)
Food packaging is a significant contributor to plastic waste, prompting a search for sustainable alternatives. Among these alternatives, modified starch-based materials have emerged as promising solutions due to their biodegradability, renewability, and abundance. However, the hydrophilic nature, poor mechanical properties, and limited thermal stability of native starch pose challenges for its use in food packaging. This review explores various modification techniques—chemical, physical, and enzymatic—that enhance the performance of starch-based materials for food packaging. The methods discussed include acetylation, crosslinking, heat-moisture treatments, and enzymatic hydrolysis, each improving the material's strength, flexibility, and barrier properties. Results demonstrate that starch modifications significantly improve the mechanical, thermal, and water vapor barrier properties of packaging films. Notably, the combination of modified starch with other biopolymers such as chitosan or gelatin further enhances these properties, making them suitable for active packaging applications. The incorporation of antimicrobial agents and nanofillers into starch-based films has expanded their functionality, enabling food shelf-life extension and quality monitoring. Despite these advancements, challenges remain in balancing the biodegradability and durability of starch-based films. Future research should focus on optimizing modification processes, enhancing scalability, and addressing regulatory concerns to ensure the commercial viability of modified starch as an eco-friendly packaging material.